The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.14716/ijtech.v7i8.6891
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence Model and Validation of Air Flow in Wind Tunnel

Abstract: As an initial analysis, numerical simulation has more advantages in saving time and costs regarding experiments. For example, variations in flow conditions and geometry can be adjusted easily to obtain results. Computational fluid dynamics (CFD) methods, such as the k-ε model, renormalization group (RNG) k-ε model and reynolds stress model (RSM), are widely used to conduct research on different objects and conditions. Choosing the appropriate model helps produce and develop constant values. Modeling studies as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The comparative study of the Standard k-ε with RNG k-ε and RSM was conducted to analyse the turbulence properties such as k, ε, and eddy viscosity. This study found that the Standard k-ε gave an effective prediction about the pressure and velocity of air in the wind tunnel as studied by Ramdlan et al, [22]. Whereas in case of cross flow turbine nozzle, Pujowidodo et al, [23] found that the RSM model has a good agreement than standard k-ε and RNG k-ε.…”
Section: Introductionmentioning
confidence: 72%
“…The comparative study of the Standard k-ε with RNG k-ε and RSM was conducted to analyse the turbulence properties such as k, ε, and eddy viscosity. This study found that the Standard k-ε gave an effective prediction about the pressure and velocity of air in the wind tunnel as studied by Ramdlan et al, [22]. Whereas in case of cross flow turbine nozzle, Pujowidodo et al, [23] found that the RSM model has a good agreement than standard k-ε and RNG k-ε.…”
Section: Introductionmentioning
confidence: 72%
“…Computational Fluid Dynamics (CFD) employs sophisticated algorithms to predict various fluid phenomena, making it a vital tool for analyzing fluid flows, including turbulence, heat transfer, particle dispersion, phase changes, and chemical reactions [1][2][3][4]. Researchers and practitioners extensively utilize CFD to optimize equipment performance, investigate failures, and improve operational parameters [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%